Assessing the Sustainability Index of the Environmental, Economic, and Social Aspects in Community-Based Tourism - Ratna Amini; Herdis Herdiansyah; Evi Gravitiani (Jurnal Ilmu Lingkungan, 2026)
Community-based tourism promotes sustainable development through local participation, yet achieving long-term sustainability remains challenging due to interconnected environmental, economic, and social factors. This study evaluates community-based tourism sustainability at Agro Eduwisata Organik Mulyaharja, a mixed-methods approach was employed. Data were collected using questionnaires, interview guides, and observations. Data analysis using Multi-Aspect Sustainability Analysis (MSA) across three dimensions. Following MSA protocols, 21 stakeholders were purposively selected based on their direct involvement in destination management. Results show environmental sustainability (57.14), while economic (35.71) and social (50.00) aspectsm fall into low sustainability categories, yielding an overall index of 47.62. Leverage analysis identifies waste/water management, tourist visitation, accessibility, and visitor satisfaction as critical intervention points. This study contributes an integrated MSA framework for rural community-based tourism assessment and provides practical guidance for targeted sustainability improvements.